Production of Recombinant Vaccine Cb Peritrophin-42 of Screwworm Fly in Escherichia coli and Saccharomyces cerevisiae (Indonesian Society for microbiology, 2007)
The screwworm fly (Chrysomya bezziana) larva is an obligate parasite which causes myasis in mammals. Vaccination is thought to be a protective and an enviromentally friendly method for combating the pest. A gene encoding a peritrophic membrane protein Cb peritrophin-42 of C. bezziana was cloned and expressed in Escherichia coli and Saccharomyces cerevisiae.Cb peritrophin-42 fused with the outer membrane protein A signal sequence was produced as an aggregate in E. coli. Expression of an Cb peritrophin-42 gene fused with oligonucleotide of the invertase signal sequence in S. cerevisiae allowed the production of 14.4 mg l-1 soluble extracellular Cb peritrophin-42. Sheep vaccinated with recombinant Cb peritrophin-42 showed a strong immunological reaction. In vivo assay following vaccination with the recombinant Cb peritrophin-42 showed a 27% reduction in the weight of recovered larvae.